Folic acid, dietary habits, and homocysteine levels in relation to neural tube defects: A case–control study in North India. Issue 14 (16th August 2018) - Deb, Roumi; Arora, Jyoti; Samtani, Ratika; Garg, Gaurav; Saksena, Deepti; Sharma, Noopur; Kumar Kalla, Aloke; Nava Saraswathy, Kallur
Abstract : Purpose: The present study attempts to understand the complex contribution of biochemical (plasma homocysteine) and nutritional parameters (dietary pattern and folate supplementation) to the neural tube defects (NTDs) affected pregnancies and controls in North Indian population. Methods: Case–control study design was adopted to assess the role of folic acid, dietary habits, and homocysteine in relation to NTD births. The subjects comprised of 130 mothers of affected children (cases) and 233 mothers of healthy children (controls), who were either carrying NTD fetus or gave birth to NTD child. Results: The mean homocysteine levels were elevated in cases (15.71 ± 8.35 μmol/L) as compared to controls (12.87 ± 5.95 μmol/L) but were lower among the non‐vergetarians (13.55 ± 6.64 μmol/L) than the vegetarians (14.78 ± 7.93 μmol/L). Vegetarian dietary habit increased the NTD risk by 1.6 fold (95% CI = 1.0–2.7) while folic acid supplementation demonstrated a protective effect for conceptions (OR = 0.59; 95% CI = 0.3–0.9). Consumption of folic acid with non‐vegetarian diet witnessed lowering of homocysteine in cases (12.88 ± 6.81 μmol/L) and in controls (11.85 ± 5.54 μmol/L), with an odds ratio depicting a 3.1 fold risk for consuming vegetarian diet without folic acid supplementation during the peri‐conceptional period. Conclusion: It is suggested that plasma hyperhomocysteinemia bears negative impact on child‐bearing women group, of north Indian ancestry, in modulating the risk of NTDs. Efforts should be made to enhance awareness regarding folic acid and vitamin B12 (non‐vegetarian diet) supplementations alongwith proper nutritional intake among women, especially those consuming vegetarian diet to control homocysteine levels in order to reduce the risk of NTDs.